Ikhwān al-Ṣafā’ and the earliest commentaries on the Ṣefer Yeẓīra - Callataÿ, Godefroid de (Journal of Jewish studies, 2024)
Modern scholarship has revealed that the impact of the Ikhwān al-Ṣafā’ in the general history of ideas was more extended, ramified and lasting than previously assumed, and that it needs to be significantly re-evaluated. As part of this broad phenomenon, it is also becoming increasingly clear today that the Brethren of Purity left a profound mark on Jewish thought throughout the Middle Ages and that their influence was not restricted to a particular place but widely disseminated across the diaspora. The present article is another contribution to this field, resolutely focused on contemporary material. Its purpose is to reconsider the possible influence of the Rasā’il Ikhwān al-Ṣafā’ on three commentaries on the Ṣefer Yeẓīra (Book of Creation) which were all written during the tenth century, respectively by Sa‘adya Gaon (d. 942), Dūnash ben Tamīm (d. after 955/6) and Shabbetay Donnolo (d. c. 982).